Wastewater monitoring and treatment for metal finishing process - Ismail Hashim (2011)
Wastewater from metal finishing industries contains contaminants such as heavy metals, organic substances, cyanides, and suspended solids, at levels which are hazardous to the environment and pose potential health risks to the public.